Comparison of lipase production on crambe oil and meal by Fusarium sp (Gibberella fujikuroi complex) - Oliveira, Bruno H. [UNESP]; Coradi, Gilberto V. [UNESP]; Attili-Angelis, Derlene; Scauri, Carolina [UNESP]; Luques, Ana Helena P. G. [UNESP]; Barbosa, Aneli M.; Dekker, Robert F. H.; Oliva Neto, Pedro de [UNESP]; Lima, Valeria M. G. [UNESP] (Wiley-Blackwell, 2013)
This study provides a comparison of fermentation conditions for the production lipases by Fusarium sp. (Gibberella fujikuroi complex) isolate FCLA-MA-41 in submerged (SmF) and solid-state fermentation (SSF) using agro-industrial residues. To assess SmF, a univariate study of seven carbon sources (crambe, corn, linseed, olive, palm (dende), soybean oils and chicken fat) and four nitrogen sources (ammonium sulfate, sodium nitrate, urea, yeast extract) was performed. The relationship among the concentrations of carbon and nitrogen sources, Triton X-100 and yeast extract was studied using a Central Composite Design (CCD). To assess SSF, different residues (sugarcane bagasse) and oil-seed meals (castorbean, corn, crambe, soybean) with additional supplements added (minimum salts, seed oils) were examined. Based on the CCD matrix, a medium containing crambe oil (17.5mL/L), Triton X-100 (5g/L), ammonium sulfate (5g/L) and yeast extract (1g/L) was proposed, resulting in a lipase titer of 3.0 +/- 0.25U/mL. The cost/production relationship was 7.73% less expensive than SmF with corn oil. SSF produced a maximum lipase titer of 5.0 +/- 0.25U/gds on crambe meal moistened with phosphate buffer. The best cost/enzyme activity estimate was for SSF with crambe meal as substrate in only distilled water (87.27% less expensive than SmF).
Keywords: Central composite design; Corn oil; Chicken fat; Ammonium sulfate; Triton X-100